The 29 October 2018 storm in Northern Italy: Its multiple actions in the Ligurian Sea. (February 2022) - Cavaleri, Luigi; Barbariol, Francesco; Bertotti, Luciana; Besio, Giovanni; Ferrari, Francesco
Highlights: Predictability of the explosive cyclogenesis and its consequences. Orography was instrumental in shaping the local wind and wave conditions. Coasts were hit by two heavy, but different, wave systems within a few hours. The local conditions were extremely sensitive to minor changes of the minimum position. Abstract: We analyse the storm that hit the Ligurian Sea in the afternoon of 29 October 2018. Although not a historical extreme, the event was unique in itself for the superposition of an explosive cyclogenesis on a preexisting southerly flow. Combined with the general meteorological pattern, this led in the range of a few hours to quite different, similarly severe wind and wave conditions. The storm has been analysed using both the models of the European Centre for Medium-Range Weather Forecasts and a nested WRF + WW3 one. The orography of Corsica has been instrumental in shaping the local fields. The storm, and in particular the cyclogenesis, were well forecast. However, as evidenced especially by the different ensemble members, minor differences in the position of the minimum could lead to substantial differences at specific locations, also where major damages were reported.